Genome-Wide Comparative Analysis of HIF Binding Sites in Cyprinus Carpio for In Silico Identification of Functional Hypoxia Response Elements - Rashid, Iliyas; Pathak, Ajey Kumar; Kumar, Ravindra; Srivastava, Prachi; Singh, Mahender; Murali, S; Kushwaha, Basdeo (Frontiers in Genetics, 2019)
Cyprinus carpio is world’s most widely distributed freshwater species highly used in aquaculture. It is a hypoxia-tolerant species as it lives in oxygen-deficient environment for a long period. The tolerance potential of an animal against hypoxia relates it to induced gene expression, where a hypoxia-inducible factor (HIF) binds to a transcriptionally active site, hypoxia response element (HRE), a 5-base short motif that lies within the promoter/enhancer region of a certain gene, for inducing gene expression and preventing/minimizing hypoxia effects. HRE is functionally active when it contains another motif, the hypoxia ancillary sequence (HAS), which is typically adjacent to downstream of HRE within 7- to 15-nt space. Here, an attempt was made for mining HRE and identifying functional HIF binding sites (HBS) in a genome-wide analysis of C. carpio. For this, gene information along with the 5,000-nt upstream (−4,900 to +100) sequences of 31,466 protein coding genes was downloaded from “Gene” and “RefSeq” databases. Analysis was performed after filtration of the impracticable genes. A total of 116,148 HRE consensus sequences were mined from 29,545 genes in different promoter regions. HRE with HAS consensus motifs were found in the promoter region of 9,589 genes. Further, the already reported genes for hypoxia response in humans and zebrafish were reanalyzed for detecting HRE sites in their promoters and used for comparative analysis with gene promoters of C. carpio for providing support to identify functional HBS in the gene promoter of C. carpio. An interactive user interface HREExplorer was developed for presenting the results on the World Wide Web and visualizing possible HBS in protein coding genes in C. carpio and displaying the comparative results along with the reported hypoxia-responsive genes of zebrafish and reported hypoxia-inducible genes in humans. In this study, a set of Perl program was written for the compilation and analysis of information that might be used for a similar study in other species. This novel work may provide a workbench for analyzing the promoter regions of hypoxia-responsive genes.